From The Accounting of War to the Accounting of Peace: Putting Bricks for a New Environmental Accounting. A Critical Analysis - Paul Diaconu (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This paper critically examines the potential movement from accounting of war to accounting of peace. The 20th century capitalist economy developed in the war, and also stimulated the war. In contradiction with the current state of facts, some economists such as Vandana Shiva promote the idea of creating an earth democracy, which is intended to accept equality of rights between the humans and other species, and to organize life so that to protect the environment against any human aggression. Accounting, as a tool of evaluation and presentation of economic information, was involved directly in the manifestation of human aggression, under its various forms, in the capitalist society. By considering as main value the concept of profit, a whole range of issues related to the environmental preservation and the limitation of natural resource were neglected. Thus, the accounting presented the resources under the form of operating costs, and not as capital. Nature was considered as an unlimited resource, and not as a value that should be kept and maintained in the future. The new paradigm might be called accounting of peace. The paper discusses how accounting has to redefine its concepts to support earth democracy and the proposed natural sustainable economy. Accounting, as a tool of force for war, did nothing but stimulate the aggressive behaviour of the world leaders, and also of the multinational corporations.
Keywords: Q01; M41; 650; accounting of war; accounting of peace; earth democracy; globalization; sustainability